Methodology and Indigenous memory: using photographs to anchor critical reflections on Indian residential school experiences. Issue 4 (20th October 2021) - Giancarlo, Alexandra; Forsyth, Janice; Te Hiwi, Braden; McKee, Taylor
Abstract : In this paper, we discuss the theoretical foundations, methodology, and method for a now-underway historical Indigenous sport photo elicitation project. In our photo elicitation sessions with former members of the Sioux Lookout Black Hawks, an Indian residential school (boarding school) hockey team that famously toured Ontario, Canada in 1951, we use photo elicitation to spark memories and provide a sense of immediacy for participants, most of whom are in their eighties. Our approach, centred around storytelling and other Indigenous methodologies contributes to the growing field of visual repatriation, in which historical images from museum or private collections are returned to source communities for re-interpretation, while also extending the notion of 'repatriation' to mean returning the power to tell stories in ways that make sense to community members, called 'restorying' (Corntassel et al. 2009 ). The photo elicitation technique prompts new reflections on the team's tour and assimilation, perspectives on cultural identity 'then' and 'now, ' and lessons for today's Indigenous youth. We examine initial research findings to evaluate the potential effectiveness of our framework that aims to place the power to tell their story firmly back in the survivors' hands, some seventy years after the fact.